2013
DOI: 10.1021/es302730h
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of BrCl, Br2, BrOCl, Br2O, and HOBr Toward Dimethenamid in Solutions of Bromide + Aqueous Free Chlorine

Abstract: HOBr, formed via oxidation of bromide by free available chlorine (FAC), is frequently assumed to be the sole species responsible for generating brominated disinfection byproducts (DBPs). Our studies reveal that BrCl, Br(2), BrOCl, and Br(2)O can also serve as brominating agents of the herbicide dimethenamid in solutions of bromide to which FAC was added. Conditions affecting bromine speciation (pH, total free bromine concentration ([HOBr](T)), [Cl(-)], and [FAC](o)) were systematically varied, and rates of dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
101
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(112 citation statements)
references
References 59 publications
11
101
0
Order By: Relevance
“…It is conceivable that steric factors might be also influencing the rate of electrophilic aromatic bromination, since one would have expected greater polarizability in suspected bromination species, H 2 O + -Br and Br 2 compared to the chlorine analogues. 3 Nevertheless selectively dibrominated pyrido-, azepino-and azocino [1,2-a] ring-fused benzimidazoles 4m-4o were isolated in high yields of 70-86%. Monitoring the reaction of 1l with H 2 O 2 -HBr using 1 H NMR showed after 20 minutes the formation of a mixture of monobromides; 5-and 7-bromobenzimidazoles in an approximate 1:3 ratio and after 20 hours a mixture of di-and tribromides 4l and 5l remained in an approximate 2:1 ratio.…”
Section: Scheme 1 One-pot Ring-fused Benzimidazole Formation With Armentioning
confidence: 99%
“…It is conceivable that steric factors might be also influencing the rate of electrophilic aromatic bromination, since one would have expected greater polarizability in suspected bromination species, H 2 O + -Br and Br 2 compared to the chlorine analogues. 3 Nevertheless selectively dibrominated pyrido-, azepino-and azocino [1,2-a] ring-fused benzimidazoles 4m-4o were isolated in high yields of 70-86%. Monitoring the reaction of 1l with H 2 O 2 -HBr using 1 H NMR showed after 20 minutes the formation of a mixture of monobromides; 5-and 7-bromobenzimidazoles in an approximate 1:3 ratio and after 20 hours a mixture of di-and tribromides 4l and 5l remained in an approximate 2:1 ratio.…”
Section: Scheme 1 One-pot Ring-fused Benzimidazole Formation With Armentioning
confidence: 99%
“…Although these latter bromine species are less abundant compared to HOBr, their contribution to bromination reactions have been shown to become significant under certain conditions. 46 The importance of these species as brominating agents tends to increase when organic substrates are less nucleophilic and thus less reactive towards HOBr and OBr -. 46,47 Considering the observed reactivity of the UV filters investigated in the present study (Figure 2), it can be postulated that the reactivity of the fast reacting OXY and DIOXY is less likely to involve species other than the abundant HOBr and OBr -.…”
Section: Resultsmentioning
confidence: 99%
“…46 The importance of these species as brominating agents tends to increase when organic substrates are less nucleophilic and thus less reactive towards HOBr and OBr -. 46,47 Considering the observed reactivity of the UV filters investigated in the present study (Figure 2), it can be postulated that the reactivity of the fast reacting OXY and DIOXY is less likely to involve species other than the abundant HOBr and OBr -. However, with the slower reacting AVO and OMC, which are far less nucleophilic than the benzophenone-type UV filters OXY and DIOXY, the contribution of species other than HOBr and OBr -to bromination reactions could be plausible.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the model predictions in Figure 3 suggest that seawater intrusion, and in particular the co-transport of bromide with chloride, will be problematic in terms of increasing the formation of THM4 well before the water would become unpalatable due to high TDS. Furthermore, laboratory studies have shown that high chloride concentrations can catalyze the formation of highly reactive bromine species during chlorination, which further increases the formation of brominated DBPs (29). Overall, the results in Figure 3 illustrate a new and unique challenge for drinking water treatment because there are a limited number of processes that can effectively remove bromide and seawater intrusion is expected to increase in many coastal areas due over pumping, changes in recharge, and sea-level rise (30,31).…”
Section: Application Of Thm4 Formation Models To Bromide Intrusionmentioning
confidence: 99%